2022
DOI: 10.1038/s41372-022-01431-4
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term outcomes of children with autoimmune congenital heart block treated with a combined maternal-neonatal therapy. A comparison study

Abstract: Objective The short and long-term outcomes of children with anti-Ro/La-related congenital heart block treated with a combined maternal-neonatal therapy protocol were compared with those of controls treated with other therapies.Study design Sixteen mothers were treated during pregnancy with a therapy consisting of daily oral fluorinated steroids, weekly plasma exchange and fortnightly intravenous immunoglobulins and their neonates with intravenous immunoglobulins (study group); 19 mothers were treated with fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although promising, its role in the primary prevention of CHB is yet to be defined. IVIG was proposed as a potential therapeutic agent in the management of second-degree congenital heart block, however its administration at replacement doses did not prevent the recurrence of CHB in mothers who had a previous child with CHB (6,22). None of the cases in our study received IVIG.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although promising, its role in the primary prevention of CHB is yet to be defined. IVIG was proposed as a potential therapeutic agent in the management of second-degree congenital heart block, however its administration at replacement doses did not prevent the recurrence of CHB in mothers who had a previous child with CHB (6,22). None of the cases in our study received IVIG.…”
Section: Discussionmentioning
confidence: 60%
“…In cases of a complete heart block, a high risk of intrauterine fetal demise (IUFD) and neonatal death exists. Dexamethasone and intravenous immunoglobulin (IVIG) are among the drugs commonly used in the management of these complications (6,7). Consequently, these fetuses are often delivered prematurely, while the placement of permanent pacemakers is required to ensure adequate cardiac function (8,9) Hydroxychloroquine is commonly used to treat autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The combination therapy showed a significantly lower progression from a 2nd to 3rd degree block at birth, an increase in heart rate, and a lower need of implants after birth [75]. The largest study to date with a control arm was by Rufatti et al in 2022 [75]. In this study, the patients were given either steroids, IVIG, and random plasma exchange, as opposed to the same regimen in the treatment arm, except with routine, multiple weekly exchanges throughout the pregnancy.…”
Section: Treatment Of Congenital Heart Blockmentioning
confidence: 91%
“…A more recent study compared the use of steroid, IVIG, and weekly plasmapheresis, as opposed to just single agents, in pregnant mothers. The combination therapy showed a significantly lower progression from a 2nd to 3rd degree block at birth, an increase in heart rate, and a lower need of implants after birth [75]. The largest study to date with a control arm was by Rufatti et al in 2022 [75].…”
Section: Treatment Of Congenital Heart Blockmentioning
confidence: 93%
“…Notably, Cuneo et al [51] demonstrated the feasibility, low false positive rate, and empowerment of mothers in utilizing home-based fetal heart monitoring during pregnancy. In cases of CAVB, the critical period for second-degree AVB to progress to irreversible third-degree AVB coincides with the optimal timeframe for effective intervention, which is less than 24 h [52][53][54]. By implementing twice-daily home monitoring, mothers can detect second-degree AVB and identify the therapeutic window for successful intervention to reverse the progression towards third-degree AVB [55].…”
Section: Patient Carementioning
confidence: 99%